Hospital-Acquired Pressure Injuries and Acute Skin Failure in Critical Care: A Case-Control Study. Issue 1 (January 2021) - Pittman, Joyce; Beeson, Terrie; Dillon, Jill; Yang, Ziyi; Mravec, Michelle; Malloy, Caeli; Cuddigan, Janet
Abstract : PURPOSE: The purpose of this study was to examine clinical characteristics and risk factors for critically ill patients who develop pressure injuries and identify the proportion of validated unavoidable pressure injuries associated with the proposed risk factors for acute skin failure (ASF). DESIGN: Retrospective case-control comparative study. SUBJECTS AND SETTING: The sample comprised adult critically ill participants hospitalized in critical care units such as surgical, trauma, cardiovascular surgical, cardiac, neuro, and medical intensive care and corresponding progressive care units in 5 acute care hospitals within a large Midwestern academic/teaching healthcare system. Participants who developed hospital-acquired pressure injuries (HAPIs) and patients without HAPIs (controls) were included. METHODS: A secondary analysis of data from a previous study with HAPIs and matching data for the control sample without HAPIs were obtained from the electronic health record. Descriptive and multivariate logistic regression analyses were conducted. RESULTS: The sample comprised 475 participants; 165 experienced a HAPI and acted as cases, whereas the remaining 310 acted as controls. Acute Physiology and Chronic Health Evaluation (APACHE II) mean score (23.8, 8.7%; P < .001), mortality (n = 45, 27.3%; P = .002), history of liver disease (n = 28, 17%; P < .001), and unintentional loss of 10 lb or more in 1 month (n = 20, 12%; P = .002) were higher in the HAPI group. Multivariate logistic regression analysis identified participants with respiratory failure (odds ratio [OR] = 3.00; 95% confidence interval [CI], 1.27-7.08; P = .012), renal failure (OR = 7.48; 95% CI, 3.49-16.01; P < .001), cardiac failure (OR = 4.50; 95% CI, 1.76-11.51; P = .002), severe anemia (OR = 10.89; 95% CI, 3.59-33.00; P < .001), any type of sepsis (OR = 3.15; 95% CI, 1.44-6.90; P = .004), and moisture documentation (OR = 11.89; 95% CI, 5.27-26.81; P <.001) were more likely to develop a HAPI. No differences between unavoidable HAPI, avoidable HAPI, or the control group were identified based on the proposed ASF risk factors. CONCLUSION: This study provides important information regarding avoidable and unavoidable HAPIs and ASF. Key clinical characteristics and risk factors, such as patient acuity, organ failure, tissue perfusion, sepsis, and history of prior pressure injury, are associated with avoidable and unavoidable HAPI development. In addition, we were unable to support a relationship between unavoidable HAPIs and the proposed risk factors for ASF. Unavoidability of HAPIs rests with the documentation of appropriate interventions and not necessarily with the identification of clinical risk factors.